Mycobacterium bovis genomics reveals transmission of infection between cattle and deer in Ireland. Issue 8 (18th August 2020) - Crispell, Joseph; Cassidy, Sophie; Kenny, Kevin; McGrath, Guy; Warde, Susan; Cameron, Henrietta; Rossi, Gianluigi; MacWhite, Teresa; White, Piran C. L.; Lycett, Samantha; Kao, Rowland R.; Moriarty, John; et al.
Abstract : Control of bovine tuberculosis (bTB), caused by Mycobacterium bovis, in the Republic of Ireland costs €84 million each year. Badgers are recognized as being a wildlife source for M. bovis infection of cattle. Deer are thought to act as spillover hosts for infection; however, population density is recognized as an important driver in shifting their epidemiological role, and deer populations across the country have been increasing in density and range. County Wicklow represents one specific area in the Republic of Ireland with a high density of deer that has had consistently high bTB prevalence for over a decade, despite control operations in both cattle and badgers. Our research used whole-genome sequencing of M. bovis sourced from infected cattle, deer and badgers in County Wicklow to evaluate whether the epidemiological role of deer could have shifted from spillover host to source. Our analyses reveal that cattle and deer share highly similar M. bovis strains, suggesting that transmission between these species is occurring in the area. In addition, the high level of diversity observed in the sampled deer population suggests deer may be acting as a source of infection for local cattle populations. These findings have important implications for the control and ultimate eradication of bTB in Ireland.